2012
DOI: 10.1161/hypertensionaha.111.187872
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Gelatinase-Associated Lipocalin Is a Novel Mineralocorticoid Target in the Cardiovascular System

Abstract: Abstract-Mineralocorticoid receptor (MR) activation may be deleterious to the cardiovascular system, and MR antagonists improve morbidity and mortality of patients with heart failure. However, mineralocorticoid signaling in the heart remains largely unknown. Using a pan-genomic transcriptomic analysis, we identified neutrophil gelatinase-associated lipocalin (NGAL or lipocalin 2) as a strongly induced gene in the heart of mice with conditional and targeted MR overexpression in cardiomyocytes (whereas induction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
71
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 43 publications
1
71
0
1
Order By: Relevance
“…We identified lipocalin 2 (Lcn2), also known as neutrophil gelatinase-associated lipocalin (NGAL) or 24p3, as a novel MR target in the cardiovascular system in mice, using a pangenomic analysis with dedicated transgenic animal models with targeted MR alteration in cardiomyocytes. 5 We showed that MR, as transcription factor, can bind directly the promoter of Lcn2 and controls its transcription.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…We identified lipocalin 2 (Lcn2), also known as neutrophil gelatinase-associated lipocalin (NGAL) or 24p3, as a novel MR target in the cardiovascular system in mice, using a pangenomic analysis with dedicated transgenic animal models with targeted MR alteration in cardiomyocytes. 5 We showed that MR, as transcription factor, can bind directly the promoter of Lcn2 and controls its transcription.…”
mentioning
confidence: 90%
“…We identified lipocalin 2 (Lcn2), also known as neutrophil gelatinase-associated lipocalin (NGAL) or 24p3, as a novel MR target in the cardiovascular system in mice, using a pangenomic analysis with dedicated transgenic animal models with targeted MR alteration in cardiomyocytes. 5 We showed that MR, as transcription factor, can bind directly the promoter of Lcn2 and controls its transcription.5 Lcn2 is a 25-kDa secreted glycoprotein belonging to the lipocalin superfamily, which binds small lipophilic substances. 6 Increased systemic levels and myocardial expression of Lcn2/NGAL have been reported in several experimental models and CVDs, such as HF and atherosclerosis; it is also is considered as a biomarker of renal dysfunction because its plasma and urinary concentrations increase in kidney diseases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…19 To test whether our approach allows the identification of aldosterone-regulated genes in cardiomyocytes, we first studied how aldosterone administration affects cardiac Ngal expression in Ctrl and MR-Cardio mice. As we previously described, 19 Ngal expression (mRNA and protein) was upregulated in MR-Cardio mice when compared with Ctrl mice. Aldosterone further enhanced cardiac Ngal expression in MR-cardio mice ( Figure 1).…”
Section: Specific Mr-dependent Response To Aldosteronementioning
confidence: 99%
“…In Ctrl mice, as previously published, Ngal was not regulated by aldosterone at the low dose used. 19 Thus, our strategy seems valuable to highlight genes dependent on MR activation by aldosterone in cardiomyocytes.…”
Section: Specific Mr-dependent Response To Aldosteronementioning
confidence: 99%